The Development of New Accounting History Research in Indonesia: Perkembangan Penelitian Sejarah Akuntansi di Indonesia dalam Bingkai Perspektif NAH - Nawangsari, Ajeng Tita; Hanun, Nur Ravita (Journal of Accounting Science, 2020)
This study aims to capture the development of new accounting history research in order to understand the extent to which accounting history has been carried out and the possible direction of research in the future. This study use literature review to collect the data. The result shows that the NAH research in Indonesia has been carried out such as accounting research during the colonioal period, the early era of Indonesia’s independence, the ancient java and bali period. However, the opportunity to do the New accounting history research in Indonesia is still widely open considering that Indonesia is a country with many cultures and dynamics. Some opportunities in this field are accounting research during the Islamic Kingdom and contemporary accounting research which can describe various current accounting dynamics that impact the development of accounting.